(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The Incentives legislation aims to raise the efficiency of job performance of all kinds through optimal investment of human resources and their capabilities to raise or increase and production influence and provide distinguished and creative services such as The Incentives Law of Productive Ministries Employees No. 20 of 1993 and instructions issued by ministries and relevant Facilities regarding incentives for their affiliates based on provisions Public Companies Law and the instructions of the Higher Education Fund issued by the Ministry of Higher Education and Scientific Research. The human element is the most unstable and complex element of production as it is characterized by a set of feelings and emotions that is expresses in different ways, and is reflected in the performance of work in institutions. As the difference in the motives and needs of workers the interest and obligations of people differ from one person to another, and from time to time. The research aimed to identify the role of incentive legislation in Iraq, by studying and evaluating its effectiveness and impact on performance and job creativity. For the purpose of expertise with the aspects of the subject, the research was divided into four sections, the first section dealt with the research methodology, the second section touched on the general framework of the incentive legislation impact on job creativity, the third section represented the practical side, presentation and analysis of the results, and the fourth section included a the conclusions and recommendations.